Rekonstruktion der unteren Extremität im Alter: ein interdisziplinärer Ansatz : Geriatrisches Assessment, perioperatives Management, Diagnostik und Therapieziele - Reiter, Gregor; Weil, Frederik; Thomas, Benjamin; Kühner, Clemens; Wittenberg-Rump, Gerhard; Schäfer, Amelia; Grützner, Paul Alfred; Kneser, Ulrich (Der Chirurg, 2019)
Complex injuries of the lower extremities in geriatric patients with multiple pre-existing comorbidities represent an increasing challenge to an interdisciplinary team of surgeons. Functional reconstruction of the extremity through osteosynthesis, revascularization and defect coverage aims to preserve mobility and achieve an early return to activities of daily life at home, while avoiding major amputation and the associated risks regarding morbidity and mortality. An interdisciplinary assessment of geriatric patients regarding dystrophy of soft tissue and skín, cardiovascular and metabolic comorbidities as well as specific geriatric diagnostics are crucial steps in ensuring favorable outcomes. Perioperatively, all improvable risk factors should be actively optimized and a specialized interdisciplinary approach to treatment planning (extremity board) is absolutely necessary for success of treatment. It outlines the special features of the geriatric assessment, diagnostics, perioperative management and treatment targets.